ALTERNATIVE ASSESSMENT AS A TOOL FOR IMPARTING HEBREW LEARNING SKILLS - Abu-Gweder, Aref (LLT Journal: A Journal on Language and Language Teaching, 2024)
This research explored the role of alternative assessments in highlighting students' language abilities by focusing on their strengths. Through interviews with 20 Hebrew language teachers in the Arab-Bedouin education system in Israel, the study revealed that, unlike traditional assessments, alternative methods were performance-based, student-centered, and emphasized communication over accuracy. Teachers identified authentic tasks as crucial for allowing students to assess their own learning while meeting educational goals. Key criteria for these tasks included reflecting students' interests, connecting to real-life contexts, encouraging creativity, and producing high-quality results.